Erratum to: ``Null Mannheim curves in the Minkowski 3-space $\\Bbb {E}^3_1$'' - Öztekin, Handan (My University, 2013)
In this paper, Theorem 3.2 and Proposition 3.2 in the paper which is cited in the title are corrected. We give the following Theorem 3.2* instead of Theorem 3.2 on page 111 in [1]. Its proof had been done in [2].
Keywords: Matematik; Fizik; Matematik